ANALYSIS OF IMPLEMENTATION OF MUDHARABAH AND WADIAH CONTRACTS - Yusuf Wibisono (Assets : Jurnal Ilmiah Ilmu Akuntansi, Keuangan dan Pajak, 2021)
This study aims to examine the development of the business management of KSPP Syari'ah BMT NU Randuagung, Lumajang Regency, plus an evaluation of the implementation of the Mudharabah and Wadiah contracts. This research is a qualitative descriptive study. The data was obtained from the KSPP Syari'ah BMT NU Randuagung document and the results of interviews with the Head of the Branch. KSPP Syari'ah BMT NU Randuagung implements a number of Syari'ah contracts, including Musyarakah contracts, Mudharabah contracts, Wadiah contracts, Al-Qardlul Hasan contracts, Murabahah contracts, Musyarakah contracts, Bai' Bitsamanil Ajil contracts, and Rahn contracts. In its implementation, Mudharabah contracts are applied to savings products with Mudharabah Muthlaqah contracts and financing products with all the required working capital through Mudharabah contracts. Meanwhile, Wadi'ah contracts only apply to savings products, namely time deposits with prizes with Wadi'ah Yad Al-Dhamanah contracts. The business strategy of developing cooperatives or BMT NU Randuagung combines focus and differentiation strategies. Meanwhile, the marketing strategy uses the "Marketing Mix", which is a marketing strategy that is implemented in an integrated manner. By applying a combination of 4 main variables, namely Product, Place, Price, and Promotion known as the 4Ps.